MANAJEMEN PROGRAM ACARA MUSIK METAL SMASH YOUR ASS DI SOLO RADIO SURAKARTA - Dian Esti Nurati, Taufik Pramestia Utama, Bedjo Sukarno & (Transformasi, 2016)
Program Smash Your Ass is one of the special programs featured in the Solo Radio broadcastedonly once a week ie every Thursday at 10 pm and specifically to provide information and playmetal music, which becomes interesting in the program Smash Your Ass this only provideinformation and play metal songs. in the solo city jonly one program that carries similar themesin Indonesia alone even if they rarely any metal music program like Smash Your Ass. During theresearch, the writer interviewed the people involved in the production as the informants, did thedirect observation to the field of research, and did the literature study. The writer aimed to digdeeper on the works of radio production in Indonesia and the management of radio as well.Based on the research result, the management in production process of Smash Your Ass programis already in line with the four management function. However, in its application the productionresults have not yet effective and efficient. It is on the writer’s best interest to make this researcha useful additional reference and a little contribution for the study of management production ofradio program, as well as to give more understanding about the world of radio in Indonesia.Keywords: production management, radio station, descriptive